ANALISIS PENDAPATAN DAN PEMASARAN KAKAO DI KECAMATAN BULOK KABUPATEN TANGGAMUS - Stella Ayu Anggraeni; Fembriarti Erry Prasmatiwi; Suriaty Situmorang (Lampung University, 2018)
This research aimed to analyze the income of cocoa farming and cocoa marketing efficiency in Bulok Subdistrict of Tanggamus Regency. This research was conducted purposively in Suka Agung and Napal Village on April to May 2017. The farmer respondents were chosen randomly and the marketing agency respondents were chosen from marketing agency which was directly involved in cocoa marketing at the research area. The analysis used was quantitative descriptive method. The result showed that the income of cocoa farming of cash cost was Rp23,502,689.07 per year and the income of cocoa farming of total cost was Rp16,365,572.38 per year . The cocoa marketing system in Bulok Subdistrict of Tanggamus Regency was inefficient, because some marketing channel (50%) had producer share less than 60 percent, the value of total marketing margins was still high (36.08 %), with uneven ratio of profit margin.Key words: cocoa, farming, income, marketing